From denazification to renazification: Experiences in postwar Germany and a victimological point of view on truth and reconciliation - Kirchhoff Ferdinand Gerd (Temida)
This paper deals with some aspects of the experiences we have in a field, which is called "Transitional Justice". First, it introduces some concepts, which might be useful in dealing with the field. Then, experiences gathered in Germany after the World War and finally returning to the conceptual level, trying to give some outlook into what we can see from a victimological perspective on the problem.